Water and Sanitation in Dhaka Slums : Access, Quality, and Informality in Service Provision - Arias-Granada, Yurani; Haque, Sabrina S.; Joseph, George; Yanez-Pagans, Monica (World Bank, Washington, DC, 2018)
Urban slum residents often have worse health outcomes compared with other urbanites and even their rural counterparts. This suggests that slum residents do not always benefit from the "urban advantage" of enjoying better access to health-promoting services. Limited access to water and sanitation services in slums could contribute to poor health of slum residents. In Bangladesh, these services generally are not delivered through formal utilities, but rather through well-functioning informal markets that are operated by middlemen and local providers. This paper analyzes a household survey to examine living conditions and quality of access to water and sanitation services in small-, medium-, and large-sized slums across Dhaka, Bangladesh. The analysis finds that access to water and sanitation services is overall quite high, but these services are subject to important quality issues related to safety, reliability, and liability. Although water access is nearly universal, water services are often interrupted or sometimes inaccessible. Sanitation is commonly shared, with the average ratio being 16 households to one facility. When considering fecal sludge management, the study finds that only 2 percent of these households have access to the Joint Monitoring Programme's conceptualization of "safely managed sanitation." The paper also finds strong evidence that water and sanitation services are operated by middlemen at various stages of service provision such as installation, management, and payment collection. The paper provides a snapshot of the differential quality in access to these services based on the monetary welfare level of the household. The snapshot shows that access to water and sanitation services is highly correlated to per capita household consumption levels, although quality remains low overall within slums. Overall, it is likely that the informality of water and sanitation services may exacerbate social and environmental risk factors for poor health and well-being.